An investigation into the synthesis of azido-functionalised coumarins for application in 1, 3-dipolar "click" cycloaddition reactions. (December 2016) - Evans, Vikki; Duncanson, Philip; Motevalli, Majid; Watkinson, Michael
Abstract: A range of reported methods have been assessed for the synthesis of two coumarin fluorophores containing azides, 1a and2, for subsequent "click" modification. In the case of1a reported methods were successfully applied, but the resulting azide proved to be rather unstable and appears more suited to in-situ generation and conversion to the "click" triazole. In the case of2, reported methods for the synthesis of precursor5 were ineffective in two cases and resulted in either no bromination α-to the carbonyl or the formation of multiple unwanted side-products, some of which were isolated, 6–13 . The use of CuBr2 in excess or Br2 in 50% HBr in acetic acid did result in the isolation of5, which could be efficiently converted to2 using excess NaN3 in THF. Highlights: Reported protocols for the bromination of 3-acetyl-7-(diethylamino)-2H-chromen-2-one are evaluated. An effective protocol for the bromination of synthesis of 3-acetyl-7-(diethylamino)-2H-chromen-2-one is reported. Mild and high yielding conditions for its conversion to a 'clickable' azide are presented.